A Review and Critique of Partner Effect Research in Small Groups. (December 2014) - Ervin, Jennifer; Bonito, Joseph A.
The purpose of this review is to discuss the ways in which partner effects are examined in group contexts. We focus on social influence, as it is a common theme in group research from cognate fields such as communication, psychology, family studies, social psychology, and business. We elaborate on different conceptions of partner effects in our discussion of the social relations model (SRM), the actor–partner interdependence model (APIM), and the group actor–partner interdependence model (GAPIM), and provide a comprehensive review of the studies that have utilized these models to study groups. Following that, we discuss the ways in which partner effects research can improve our theoretical and empirical understanding of group processes.